Cynic's Dictionary - Dillon Malone Aubrey (Contemporary Books, 2000)
Wickedly funny, this collection of acerbic definitions features quotes from a range of renowned cynics who tell it like it really is. The likes of Ambrose Bierce, Mae West, and W.C. Fields are represented in this entertaining, no-holds-barred alternative dictionary.